Systematic review: Symptoms of parental depression and anxiety and offspring overweight - Paula Lobo Marco; Inaê Dutra Valério; Christian Loret de Mola Zanatti; Helen Gonçalves
ABSTRACT OBJECTIVE To evaluate the existing literature on the association between parents' depression and anxiety and their influence on their children's weight during childhood, identifying possible mechanisms involved in this association. METHODS A systematic search of the literature was conducted in the PubMed, PsycINFO and SciELO databases, using the following descriptors: (maternal OR mother* OR parent* OR paternal OR father) AND ("common mental disorder" OR "mental health" OR "mental disorder" OR "depressive disorder" OR depress* OR anxiety OR "anxiety disorder") AND (child* OR pediatric OR offspring) AND (overweight OR obes* OR "body mass index" OR BMI). A total of 1,187 articles were found after peer selection. RESULTS In total, 16 articles that met the inclusion criteria were selected for the review. Most of them investigated depressive symptoms and only three, symptoms of maternal anxiety. The evaluated studies suggested a positive association between symptoms of maternal depression and higher risk of childhood obesity. The results diverged according to the chronicity of depressive symptoms (episodic or recurrent depression) and income of the investigated country (high or middle income). Mechanisms were identified passing by quality of parenthood, affecting behaviors related to physical activity and child-feeding, as mediators of the association. CONCLUSIONS We conclude there is evidence of a positive relationship between the occurrence of maternal symptoms of depression and anxiety and childhood obesity. It is emphasized the need for a better understanding on the effect of depressive symptoms and the contextual factors involved in this relationship so that effective intervention strategies can be implemented.